2016
DOI: 10.3389/fnhum.2016.00336
|View full text |Cite
|
Sign up to set email alerts
|

Neuroethics 1995–2012. A Bibliometric Analysis of the Guiding Themes of an Emerging Research Field

Abstract: In bioethics, the first decade of the twenty-first century was characterized by the emergence of interest in the ethical, legal, and social aspects of neuroscience research. At the same time an ongoing extension of the topics and phenomena addressed by neuroscientists was observed alongside its rise as one of the leading disciplines in the biomedical science. One of these phenomena addressed by neuroscientists and moral psychologists was the neural processes involved in moral decision-making. Today both strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 47 publications
0
27
0
1
Order By: Relevance
“…A study used a card-guessing task [ 64 ] to observe the differences in coding on the expected value of winnings and losses, distinguishing the effects of probability and magnitude of the results: in individuals with AUD, a more pronounced neural response in the left caudate nucleus (CN) was present during the anticipation of winning and in the left CN and left putamen in relation to the magnitude of the results. A general imbalance in the conflict-monitoring brain circuitry underlying decision-making under risk has been described in AUD: specifically, patients with AUD showed enhanced anticipatory activity in neural circuitries of executive and motor control, encompassing the insula (INS), the ACC and the basal ganglia [ 58 , 65 , 66 ]. In addition, recent studies have demonstrated that the dorso lateral prefrontal cortex (DLPFC) may be particularly hyperactive in individuals with AUD during delayed and cognitively difficult decisions [ 67 ].…”
Section: Neurobiological and Neurofunctional Alterations In Gd Andmentioning
confidence: 99%
“…A study used a card-guessing task [ 64 ] to observe the differences in coding on the expected value of winnings and losses, distinguishing the effects of probability and magnitude of the results: in individuals with AUD, a more pronounced neural response in the left caudate nucleus (CN) was present during the anticipation of winning and in the left CN and left putamen in relation to the magnitude of the results. A general imbalance in the conflict-monitoring brain circuitry underlying decision-making under risk has been described in AUD: specifically, patients with AUD showed enhanced anticipatory activity in neural circuitries of executive and motor control, encompassing the insula (INS), the ACC and the basal ganglia [ 58 , 65 , 66 ]. In addition, recent studies have demonstrated that the dorso lateral prefrontal cortex (DLPFC) may be particularly hyperactive in individuals with AUD during delayed and cognitively difficult decisions [ 67 ].…”
Section: Neurobiological and Neurofunctional Alterations In Gd Andmentioning
confidence: 99%
“…Neuroethics, a relatively new field of inquiry or sub-discipline (Marcus and Dana Foundation, 2002; Leefmann et al, 2016), can best be understood as an offshoot of biomedical ethics which focuses in particular on ethical issues related to the brain. It is sometimes described as consisting of two main strands: the ethics of neuroscience and the neuroscience of ethics (Roskies, 2005, p. 18).…”
Section: The Ethics Of Neuro-ictmentioning
confidence: 99%
“…Auch die 2013 gegründete Open Access-Online-Zeitschrift "Journal of Cognition and Neuroethics" hat noch keinen Impactfaktor. Möglicherweise ist diese Situation einer der Gründe, weshalb gemäß einer aktuellen bibliometrischen Studie Neuroethik-Aufsätze häufiger in biomedizinischen als in geistes-oder sozialwissenschaftlichen Zeitschriften erscheinen (Leefmann et al 2016). In Nordamerika existieren bereits spezielle Neuroethik-Forschungszentren oder größere Neuroethik-Forschungseinheiten, z.…”
Section: Während Eines Treffens Im Kalifornischen Asilomar Im Jahr 20unclassified